Pengaruh Jumlah Wajib Pajak dan Inflasi Terhadap Penerimaan Pajak Penghasilan di Indonesia - Dwi Pertiwi Anggraini (Graha Mitra Edukasi, 2022)
The purpose of this study was to determine the effect of the number of taxpayers and inflation on income tax revenues in Indonesia. The data of this research is sourced from secondary data or time series, namely from 2002 to 2020. Where the data is obtained from various sources, such as tax.go.id, www.bps.go.id and www.kemenkeu.go.id. In this study, the researchers used an associative approach quantitatively. Associative research is research that aims to determine the effect or relationship between two or more variables. data analysis is statistical in nature with the aim of testing the research hypotheses that have been determined previously. This research used multiple linear regression analysis method. Multiple linear regression using SPSS 22 software. The results of this study are the number of taxpayers has a significant effect on Income Tax in Indonesia. Inflation has no effect on Income Tax in Indonesia. Meanwhile, the number of taxpayers and inflation together affect the income tax revenue in Indonesia